Effect of Strength and Endurance Training Program on Mental and Physical Health of Spinal Cord-Injured Persons (Baltic Journal of Sport and Health Sciences, 2018)
Background. The aim of the research was to examine the eﬀects of eight weeks of strength and endurance training on the improvement of mental health and physical state of spinal cord-injured persons. Methods. Twelve persons with spinal cord injury (SCI) participated in an eight-week intervention program of mainly two training types: strength and wheelchair driving endurance training. Subjects with SCI represented the experimental and control groups. The mental (Ware, 2000) and physical (isometric strength of the hand grip, strength of the shoulders and arms bench press, aerobic endurance 12 min and anaerobic endurance 30 s driving the wheelchair tests) values were evaluated before and after the program. Results. After the primary questioning of the experimental group participants before organizing strength and endurance training program and the fnal questioning after the program, it was revealed that most values of mental health improved. The physical state characteristics of persons with spinal cord injury revealed diﬀerences between pre-test and post-test values. Conclusions. This study indicated that persons with spinal cord injury involved in eight weeks strength and endurance training program improved mental and physical health parameters in comparison with persons with spinal cord injury not participating in any training program. Isometric force and 12 min wheelchair driving are good markers for strength, power and endurance in persons with spinal cord injury.Keywords: strength and endurance training, psychical and physical health, spinal cord-injured persons.